Challenges and Facilitators to Patient and Public Involvement In Stroke Research: Protocol for a Qualitative Study - Hamidreza Khankeh; Shima Shirozhan; Ulrich Dirnagl (Health Expectations)
ABSTRACT Background Patient and public involvement in the research process, despite its novelty and importance in enhancing the quality of studies, still has many unknown dimensions that need to be discovered and explained through qualitative research. Conducting qualitative research to understand experiences in newly emerging topics is challenging and can pose significant difficulties for researchers. Objective Development of a directed qualitative content analysis study protocol to identify challenges and facilitators to patient and public involvement in stroke research. Design Study protocol of qualitative content analysis. Method This study protocol outlines the step‐by‐step design for a directed qualitative content analysis. The study will use a directed approach, following the methodology proposed by Hsieh and Shannon (2005). Participants will be selected based on their experience or knowledge of involvement in the research process, including stakeholders such as researchers, people who are affected by stroke, caregivers, and healthcare providers in stroke research. Participants will be purposefully chosen for their willingness and ability to contribute. Data will be gathered through semi‐structured in‐depth interviews. The quality of the study will be ensured by applying the criteria established by Lincoln and Guba. Conclusion This study protocol offers a comprehensive guide for conducting directed qualitative content analysis, outlining the research process step‐by‐step to aid researchers using similar methodologies. It addresses common language‐related challenges and suggests solutions. The protocol emphasizes maintaining high research standards through specific criteria and provides a detailed discussion of ethical considerations. The authors advocate for publishing qualitative research protocols before implementation to improve research quality, foster ethical and integrated practices, and support novice researchers. Patient or Public Contribution Stakeholder involvement was crucial in developing the interview guide. Feedback was gathered from six experts: three researchers (quantitative and qualitative fields), one stroke rehabilitation specialist, and two Patient and Public Involvement (PPI) experts. Their insights guided the research team in determining research areas, proposing participant recruitment strategies, addressing language barriers, and ensuring necessary details were provided for the study protocol.